Development and study of mucoadhesive microcapsules for the nasal levodopa delivery - D. S. Gordeeva; V. V. Khutoryanskiy; R. I. Moustafine (Разработка и регистрация лекарственных средств, 2024)
Introduction. Microparticles are of great interest for use in various drug delivery systems. The intranasal route of administration holds a special place due to its several advantages, including ease of use, minimal side effects, and the ability for rapid delivery of drug directly to the brain. The drug in the microparticles acts locally, thereby ensuring the release of the drug in the required amount in the target organ. The drug from the nose enters directly into the brain through the olfactory region along the sensory nerves. The development of microparticles with the ability to mucoadhesion on the surface of the nasal mucosa will increase the bioavailability of drugs used in the treatment of diseases and disorders of the central nervous system (CNS).Aim. Development and study of microcapsules with mucoadhesive properties for the intranasal delivery system of levodopa.Materials and methods. Microcapsules (MC) were obtained by ultrasonic electrospraying method on a B-390 encapsulator (BUCHI, Switzerland) followed by filtration under vacuum, washing with deionized water and freeze-drying at –50 °C and 0.05 mBar for 48 h in a FreeZone 1 L dryer (Labconco, USA). The structural features of MC were studied by optical microscopy using Evident CX33 microscope with high-resolution camera (Olympus, Japan). For evaluation of the images, we used ImageView™ software (version x64, 4.11.22376.20230402). Morphology of prepared microcapsules were also detected using a portable ultraviolet light source (Jialitte F114, China) by a digital USB microscope (OT-INL40 1000X, China). The mucoadhesive properties of sodium fluoresceinate-loaded MC were studied using isolated sheep nasal mucosa in an SI60 incubator (Stuart, UK) at 37.0 ± 0.5 °C. Fluorescent images were obtained using a TLC Visualizer 3 high-resolution imaging system (CAMAG®, Switzerland). ImageJ 1.53e software (ImageJ, USA) was used to process the obtained macroscopic images and plot graphs. The encapsulation efficiency, % (EE%) and loading capacity, % (LC%) of levodopa loaded MC were assessed using UV spectrophotometry on an Evolution™ 220 device (Thermo Fisher Scientific, USA) at a wavelength of 202 nm. The release of levodopa from MC was performed using a CE 7smart flow cell (SOTAX AG, Switzerland), method IV (State Pharmacopoeia XV of the Russian Federation), at a temperature of 37 ± 0.5 °C for 3 hours in an artificial nasal fluid (ANF) medium. The amount of released drug was determined using an Evolution™ 220 UV spectrophotometer (Thermo Fisher Scientific, USA) at a wavelength of 202 nm.Results and discussion. A method for MC preparation was developed, the device parameters and the optimal composition of microparticles were selected. Two types of MC were obtained: alginate MC and MC coated with Eudragit® EPO (EPO), which have mucoadhesive properties. The average diameter of alginate MC was 0.365 ± 0.018 mm, EPO-coated MC – 0.426 ± 0.017 mm. Alginate MC are washed off the surface of isolated sheep nasal mucosa 5 minutes after irrigation with ANF, and EPO-coated are retained for 1 hour. EE% of MC with levodopa is above 90 %. LC% of EPO-coated is higher than that of alginate MC. The release of levodopa into the ANF medium from EPO-coated MC was 100 % after just 30 minutes of the study, while for alginate MC it was no more than 60 ± 6.1 % after 3 hours.Conclusion. EPO-coated MCs exhibit mucoadhesive properties on the nasal mucosa surface and their further study is promising for use in intranasal levodopa delivery systems.